Prescribed performance adaptive event-triggered consensus control for multiagent systems with input saturation - Yue, Xia; Liu, Jiarui; Chen, Kairui; Zhang, Yuanqing; Hu, Zikai (Frontiers in Neurorobotics, 2023)
Focus on a class of multiagent systems with input dead-zone and saturation, a prescribed performance adaptive event-triggered consensus control method is developed. In practical engineering applications, systems are inevitably suffered from input saturation. Besides, input dead-zone is widely existing. As the larger signal is limited and the smaller signal is difficult to effectively operate, systems efficacious input encounters unknown magnitude limitations, which seriously impact systems control performance and even lead to systems instability. Furthermore, when constrained multiagent systems are required to converge quickly, the followers would achieve it with drastic and quick variation of states, which may violate the constraints and even cause security problems. To address those problems, an adaptive event-triggered consensus control is proposed. By constructing the transform function and the barrier Lyapunov function, while state constrained is guaranteed, multiagent systems quickly converge with prescribed performance. Finally, some examples are adopted to confirm the effectiveness of the proposed control method.